2002
DOI: 10.1097/00001199-200204000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Social Work Liaison Program on Family Caregivers to People with Brain Injury

Abstract: This research suggests that a relatively low-cost, nonintensive intervention may offer substantial benefit to families caring for people with brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
1
42
0
1
Order By: Relevance
“…Primary caregivers of TBI patients experience considerable emotional stress and sense of burden. Albert et al [44] showed that low-cost interventions relieve the burden of caregivers and improve their satisfaction. A study by Sinnakaruppan et al [45] showed that family education programs for caregivers and TBI family members help relieve stress and strengthen coping abilities.…”
Section: Tbi Benefits From Behavioral Emotional and Family Theramentioning
confidence: 99%
“…Primary caregivers of TBI patients experience considerable emotional stress and sense of burden. Albert et al [44] showed that low-cost interventions relieve the burden of caregivers and improve their satisfaction. A study by Sinnakaruppan et al [45] showed that family education programs for caregivers and TBI family members help relieve stress and strengthen coping abilities.…”
Section: Tbi Benefits From Behavioral Emotional and Family Theramentioning
confidence: 99%
“…11,12,21,23,24 Studies that have examined the effectiveness of homebased clinician facilitated problem-solving support intervention programs for TBI caregivers when compared with receipt of educational materials only show significant decrease in caregiver depression, health complaints, and dysfunctional problem-solving styles over time. 25,26 …”
Section: Caregiver Support Groupsmentioning
confidence: 99%
“…Probably efficacious [Conoley and Sheridan, 1996;Albert et al, 2002;Leith et al, 2004;Boschen et al, 2007;Glang et al, 2007] …”
Section: Match the Intervention To The Familymentioning
confidence: 99%
“…Although Boschen et al's [2007] conclusions were limited by the methodology and marginal results of existing studies, they suggest that advocacy may facilitate increased family access to services, delivery of additional education to caregivers, and addressing of otherwise ignored concerns. Studies of adults with BI suggest that providing a social work liaison to caregivers of individuals with BI after hospital discharge has benefits in reducing caregivers' sense of burden, increasing caregivers' life satisfaction, and helping caregivers feel increased mastery over rehabilitation outcomes [Albert et al, 2002]. Glang et al [2007] investigated an educational advocacy intervention program where parents of children with BI were taught educational advocacy skills via an innovative CD-ROM based program.…”
Section: Provide Advocacymentioning
confidence: 99%